2018
DOI: 10.1007/s00296-018-4066-5
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease in Spanish paediatric population and synoptic weather types: an observational study

Abstract: Kawasaki disease (KD) is a vasculitis of unelucidated pathogenesis that usually occurs in paediatric patients. In this study we analyse the temporal pattern and geographical distribution of the disease in Spain, and its relationship with atmospheric circulation patterns. We performed a retrospective study in which we collected all hospital admissions due to KD in the country between 2005 and 2015 and explored their relationship with demographic and geographical characteristics. Moreover, we calculated daily su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…From 2000 to 2011, KD cases ranged from 30 to 50 per year in Portugal, with a mean of 39 cases per year (35). The (19,27,29). A study performed from 1981 to 2013 in the University hospital of Lausanne in Switzerland described an increase in number of KD cases since 1981.…”
Section: Time Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2000 to 2011, KD cases ranged from 30 to 50 per year in Portugal, with a mean of 39 cases per year (35). The (19,27,29). A study performed from 1981 to 2013 in the University hospital of Lausanne in Switzerland described an increase in number of KD cases since 1981.…”
Section: Time Trendsmentioning
confidence: 99%
“…These observations underline the importance of the methodology in interpreting results. European studies based on hospital discharge data published in the last 10 years showed annual incidence rates of 9.1–14.7 per 100 000 children under 5 years old ( 19 , 25 , 27 , 28 ), whereas those based on prospective surveillance found lower rates ( 26 , 29 ) ( Table 1 ). A prospective surveillance design in Germany with cross validation with hospital records from two states found that the hospital-based German Pediatric Surveillance Unit (ESPED) missed 37–44% of cases.…”
Section: Incidence Ratesmentioning
confidence: 99%
“…In Spain, the first population-based study on the epidemiology of KD was published by the KD Catalonian Working Group reporting a mean annual incidence in Catalonia of 3.5/100,000 children <14 years old and 8/100,000 children <5 years (2004–2013)[13]. More recently an incidence of 11.7/100,000 children <5 years has been reported (2005–2015) for the whole of Spain, but this study was a retrospective ecological study and may be overestimating the real incidence[14,15]. Surveillance KD studies are important to monitor trends and outcomes of the disease.…”
Section: Introductionmentioning
confidence: 99%